Kepemimpinan Kepala Sekolah di Era New Normal pada Madrasah Tsanawiyah Negeri 1 Aceh Jaya - Junias Zulfahmi; Rosi Roswita (Program Studi Manajemen Pendidikan Islam, 2022)
This study examines the leadership of the principal in the new normal era at MTsN 1 Aceh Jaya. This study used a qualitative approach with data collection techniques using observation, interviews, and documentation, while the data analysis techniques used descriptive methods with an inductive approach. The results of this study indicate that the leadership of the principal in the new normal era at MTsN 1 Aceh Jaya can be seen from several stages including planning, implementation, and supervision. The planning stage is based on the Joint Decree of the 4 Ministers on the Implementation of Learning in the Covid-19 Pandemic Period. The implementation is carried out in collaboration between parents and schools, where the school before carrying out the learning process holds a meeting with parents about the policy of face-to-face learning in the new normal era. The implementation is in an online form, namely through WhatsApp group media, while face-to-face through the division of shifts, namely shift A and shift B on the condition that they comply with health protocols. The principal supervises teachers and students by looking at the attendance of teachers and students and visiting the teacher's room and student class.